Chromium-Catalyzed Reductive Cleavage of Unactivated Aromatic and Benzylic C–O Bonds - Yuan, Shuqing; Ling, Liang; Tang, Jinghua; Luo, Meiming; Zeng, Xiaoming (Synthesis, 2021)
Reductive cleavage of aromatic and benzylic C–O bonds by chromium catalysis is reported. This deoxygenative reaction was promoted by low-cost CrCl2 precatalyst combined with poly(methyl hydrogen siloxane) as the mild reducing agent, providing a strategy in forming reduced motifs by cleavage of unactivated C–O bonds. A range of functional groups such as bromide, chloride, fluoride, hydroxyl, amino, and alkoxycarbonyl can be retained in the reduction.
Keywords: C–O bond; reduction; chromium; homogeneous catalysis